Soil Organic Carbon, Hydraulic Properties and Yield of Maize and Wheat under Long–term Fertilization in an Inceptisol - D. Chakraborty, R.K. Tomar and M.C. Meena, A. Thangasamy, Dhyan Singh (Journal of the Indian Society of Soil Science, 2017)
The present investigation was carried out to evaluate the changes in oxidizable soil organic carbon (SOC), hydraulic properties and yield of both maize (Zea mays) and wheat (Triticum aestivum) under long–term fertilization during 34th cropping cycle. Six fertilizer treatments were selected for the present study. The soil samples were analyzed for oxidizable SOC, bulk density (BD), mean weight diameter (MWD), soil water retention at 33 and 1500 kPa, saturated hydraulic conductivity (Ksat) at surface (0-15 cm) and sub–surface (15–30 cm) soil layers. The plant samples were analyzed for nutrient uptake at harvest. The results showed that N and NP fertilizer treatments maintained initial oxidizable SOC and soil physical condition in surface layer, and showed significantly higher values compared with control. However, significant reductions in yield and nutrient uptake by maize and wheat were observed in these treatments compared to nitrogen, phosphorus and potassium (NPK) applied plot, nitrogen, phosphorus, potassium and sulphur (NPKS) applied plot and NPK+ farmyard manure (FYM) treatment. The NPK + FYM application significantly increased oxidizable SOC, MWD and decreased BD compared to control plots and the initial values. Balanced application of plant nutrients through mineral fertilizers and FYM increased oxidizable SOC by 84 per cent and improved soil hydraulic properties, uptake and yield of both maize and wheat compared to control. Integrated use of NPK along with FYM was the best option for sustaining soil physical condition, enhancing nutrient uptake and ultimately crop productivity.